2012
DOI: 10.1111/j.1365-2702.2011.03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Taiwanese translation and psychometric testing of the revised illness perception questionnaire for patients with traumatic injury

Abstract: Translation of the instrument into Chinese extends its utility to the traumatic injury population. Awareness of patients' illness representations can help clinicians provide appropriate interventions to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
(22 reference statements)
2
19
0
Order By: Relevance
“…Another study examined the factor structure of the IPQ‐R in patients with traumatic injury by also using a six‐factor structure, which explained 60.30% of the total item variance in the scale after removing eight items. This was very similar to the original scale . In contrast, a recent study investigating the factor structure of the Chinese IPQ‐R for substance dependence among injecting drug users found that the original IPQ‐R factor structure fit the data poorly and factors derived from an EFA also could not be interpreted .…”
Section: Discussionsupporting
confidence: 52%
“…Another study examined the factor structure of the IPQ‐R in patients with traumatic injury by also using a six‐factor structure, which explained 60.30% of the total item variance in the scale after removing eight items. This was very similar to the original scale . In contrast, a recent study investigating the factor structure of the Chinese IPQ‐R for substance dependence among injecting drug users found that the original IPQ‐R factor structure fit the data poorly and factors derived from an EFA also could not be interpreted .…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, item Tr_CR19 ("There is very little that can be done to improve my dental problem") did not load on any factor. Previous studies also removed item 19 [Cabassa et al, 2008;Chen et al, 2008;Abubakari et al, 2012] or did not include it in any factor [Wittkowski et al, 2008;Chaboyer et al, 2012]. This may be explained by people's beliefs that caries is a minor problem that can be controlled by dentists and that people cannot do anything to prevent or handle it.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, item Tr_CR23 ("There is nothing which can help my dental problem") fit to factor 7 (illness coherence). Chaboyer et al [2012] found that item Tr_Cr23 loaded on the illness coherence factor, which is probably because individuals who do not understand their dental problem may perceive their problem does not have a solution. Finally, the remaining items of the timeline-acute/chronic factor conformed to the timeline-chronic exclusive factor, and the consequences factor only lost 1 item (C8), an issue that was previously noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations